Nanoscale imaging and force probing of biomolecular systems using atomic force microscopy: from single molecules to living cells. Issue 45 (14th November 2017) - Li, Mi; Dang, Dan; Xi, Ning; Wang, Yuechao; Liu, Lianqing
Abstract : Atomic force microscopy is a powerful tool for investigating nanoscale native molecular behaviors from single molecules to living cells. Abstract : Due to the lack of adequate tools for observation, native molecular behaviors at the nanoscale have been poorly understood. The advent of atomic force microscopy (AFM) provides an exciting instrument for investigating physiological processes on individual living cells with molecular resolution, which attracts the attention of worldwide researchers. In the past few decades, AFM has been widely utilized to investigate molecular activities on diverse biological interfaces, and the performances and functions of AFM have also been continuously improved, greatly improving our understanding of the behaviors of single molecules in action and demonstrating the important role of AFM in addressing biological issues with unprecedented spatiotemporal resolution. In this article, we review the related techniques and recent progress about applying AFM to characterize biomolecular systems in situ from single molecules to living cells. The challenges and future directions are also discussed.